Studying the plant species diversity in the natural Aleepo Pine (Pinus halepensis Mill.) forest of Beit Al-Maissra (Al-Kadmous District). - مريم, سومر (Latakia University Journal -Biological Sciences Series, 2021)
This research was aimed to study the plant species diversity in the natural forest of Aleppo pine Pinus halepensis at the site of Beit Al-Maissra (Al-Kadmous District) on an area of approximately 14 hectares, which is subject to intensive human activity consisting of random cutting and overgrazing. Forest parameters have been measured and plant survey has been carried out utilizing the Intercepted Line Method. Diversity indices (Species Richness, Shannon, Sorenson) and relative importance were calculated and plant uses were determined in the two main groups of Aleppo pine. The diameter at breast height (DBH), the dominant height and the density per hectare of Aleppo pine trees were respectively (14.3 ± 1.8cm, 13 m, 600 trees) in the first group and (8.3 ± 0.8cm, 5.6 m, 700 trees) in the second group, The total number of species registered at the whole site was 46 plant species belonging to 29 families, and the number of plant species registered in the first group was 38 species belonging to 27 families, while the number of species registered in the second group was 20 plant species belonging to only 13 families and Fabaceae was the most represented family in the two groups. Shannon's index was 3.69 and 3.10 bytes in the first and second group respectively. The relative importance in the first group showed the dominance of Aleppo pine in the tree layer and Erica manipuliflora in the shrub layer and in the second group E. manipuliflora was also dominant in the shrub layer while the tree layer was absent. The study registered 7 edible species was species (15% of the total number of registered species), 18 medicinal species (38%), 17 ornamental species (36%) and 10 pastoral species (21%) in the whole site. These findings demonstrate the clear importance of the vegetation in the studied site, which justifies the need to accelerate immediate action to mitigate the degradation factors of the site and preserve its plant diversity.